Evaluating a multicomponent intervention for managing kidney outcomes among patients with moderate or advanced chronic kidney disease (CKD): protocol for the Strategies for Kidney Outcomes Prevention and Evaluation (SKOPE) randomized controlled trial - Tazeen Hasan Jafar; Ngiap Chuan Tan; Mihir Gandhi; Sungwon Yoon; Eric Finkelstein; Peter Moey Kirm Seng; Ruiheng Ong; Anandan Gerard Thiagarajah; Bing Long Lee; Ka Chi To; Aminath Shiwaza Moosa (Trials)
Abstract Background Chronic kidney disease (CKD) poses a global health challenge with high morbidity and mortality rates. Early detection and prompt intervention are critical in preventing progression to end-stage kidney disease (ESKD) and cardiovascular complications. Effective CKD management requires comprehensive care packages that integrate both pharmacological and non-pharmacological interventions within collaborative, team-based models, aiming to enhance patient outcomes and overall quality of life. The goal of the Strategies for Kidney Outcomes Prevention and Evaluation (SKOPE) study is to establish effective multicomponent intervention (MCI) strategies for evaluating and preventing kidney outcomes in patients with moderate to advanced CKD within primary care settings in Singapore. Methods This study is a 3-year randomized controlled trial among 896 participants aged between 40 and 80 years with moderate or advanced CKD in five government-subsidized polyclinics in Singapore. The components of the MCI are (1) nurses/service coordinators trained as health coaches for motivational conversation and CKD-specific lifestyle counseling on diet and exercise, using a hybrid follow-up approach of in-person, telephone, and secure video meetings; (2) training physicians in algorithm-based standardized management of CKD; (3) subsidy on SGLT2i medications for CKD; and (4) regular CKD case review meetings. The primary outcome is the estimated glomerular filtration rate (eGFR) total slope from randomization to final follow-up at 36 months. Discussion If shown to be effective, cost-effective, and acceptable, SKOPE should be considered for scaling country-wide and in similar regional healthcare systems. Trial registration ClinicalTrials.gov NCT05295368. Registered on March 25, 2022.